Optimization of parallel seam welding processing parameters for micro crystal resonator based on quadratic regression orthogonal combination method. (9th September 2020) - Hu, Jian; Xu, Lei; Xing, Saiding; Yu, Xindong; Li, Gangyan
Abstract: Parallel seam welding is the key process of micro crystal resonator packaging. The design of processing parameters mainly relayed on experience and a large number of experiments, resulting in high cost and low efficiency. In order to improve the design efficiency of parallel seam welding processing parameters of micro crystal resonator, the parallel seam welding experimental system for micro crystal resonator is designed, and the parallel seam welding current waveform is put forward by analyzing the welding defects. According to the weld morphology observation, the effective interval of processing parameter optimization was determined. Based on the quadratic regression orthogonal combination method, the micro crystal resonator air-tightness defective product ratio is used as the parallel seam welding quality evaluation index, and the regression equation about the processing parameter and the air-tightness defective product ratio are presented. The optimization scheme of parallel seam welding processing parameters of micro crystal resonator is obtained by solving the regression equation.